Accepting the avoidable death: The philosophy of limiting intensive care - Sörensen, Marc (Bioethics, 2019)
Limiting intensive care is paid increasing attention. In the echoing call for physicians’ ethical self-restriction, it is easily overlooked, however, that ethics needs a critical epistemological analysis before it can suffice as an emergency brake to futile treatment. This analysis is provided by the present essay. The authors suggest that the difficulties of resolving moral dilemmas related to limiting intensive care may just be due to the unclarified epistemological status of moral claims. Even if normative ethics cannot prescribe right decisions, but only draw conclusions from defined premises, the premises may or may not be true. Their intertwined descriptive and normative evidence is endorsed in an academic and political discourse. There will necessarily be various demands for rationality in prudent decisions between physicians, their patients and society. These demands are formulated dialogically through critical questions and justified answers. A good argument is the convincing one that, finally and ideally, leads to the absence of open objections. Thus, in the end the rightness of a given decision does not depend on axiomatic moral principles, but is comparative and conditional, as it is given in an omnilateral argument. Neither is it the democratic process of shared decision making that we should evaluate, but rather the argumentative state itself, when we judge the morality of health politics and clinical practice.